Peran Audit Internal Dalam Penerapan Peraturan Menteri Keuangan Nomor 112/PMK.03/2022 - Nadia Dwi Pratiwi; Badzlina Chaerani Putri; Irda Agustin Kustiwi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to investigate the role of internal audit in the context of implementing Minister of Finance Regulation Number 112/PMK.03/2022. These regulations have a significant impact on financial governance and accountability across various entities. With a focus on internal audit, this research explores how the internal audit function contributes to ensuring compliance with these financial regulations. This research method uses qualitative methods involving documentation analysis and interviews. The results of the research are expected to provide insight into the effectiveness of the role of internal audit in supporting the implementation of related Minister of Finance Regulations and provide recommendations for further improvements in the entity's financial management.